On Multiple Solutions of Concave and Convex Nonlinearities in Elliptic Equation on ℝN. (16th June 2009) - Chen, Kuan-Ju
Abstract : We consider the existence of multiple solutions of the elliptic equation onℝ N with concave and convex nonlinearities.